Rules and violence: on the cultural history of collective violence from Late Antiquity to the Confessional Age : [International Medieval Congress in Leeds 2012] = Regeln und Gewalt : zur Kulturgeschichte der kollektiven Gewalt von der Spätantike bis zum konfessionellen Zeitalter - Dietl, Cora; Knäpper, Titus (De Gruyter, 2014)
Beasts, burning, and beheading : show executions in late antiquity -- Murder in the palace : some considerations on assassinations in late antiquity and the early Middle-Ages -- Ripped bodies, pierced heels and burned houses : violence and its evluation in Norse saga literature -- Gewalt und gemeinschaft im Eneasroman Heinrichs von Veldeke -- More than enemies : the description of nomads in the Byzantine literature of the epoch of the first Pecheneg incursions Byzantium -- At the threshold of Hell : northern crusaders on the way to Satan's dominion -- Ehestands-Mären und gewalt : autoaggresive gewaltgemeinschaften und ihre gewalthafte transformation -- in gewaltgemeinschaften (die eingemauerte frau, frauenzucht) -- Regeln für den ,gattungsfreien raum' : generische muster der gewaltdarstellung in Hans Folz' Erzähllied vom Poss rauch -- Der ritter im baum : wahnsinn als auslöser von gewalt am beispiel des Rappoltsteiner Parzifal -- Practices of violence and their limits : the Percy-Neville feud in the 1450s -- Der überfall auf das Nördlinger scharlachrennen : gewalt und symbolische ordnung der gesellschaft in der urbanen festkultur -- Erasmus, Reuchlin und Ulrich von Hutten als ,gewaltgemeinschaft'? ein tragedia oder spill gehalten in dem künigklichen Sal zu Pariss -- Der kampf der reformatoren gegen die baalistischen pfaffen in der grafschaft Nassau-Weilburg zur zeit des Augsburger interims (1548-52/1555)